Recognition and freedom : Axel Honneth's political thought - Jakobsen, Jonas; Lysaker, Odin, 1976- (Social and critical theory ;, 2015)
Recognition and Freedom offers up-to-date discussions of Axel Honneth's political thought by ten experts in the field. It also includes an interview with Honneth and an essay by him on education and democracy, previously unpublished in English.